2023
DOI: 10.1093/eurheartj/ehad152
|View full text |Cite|
|
Sign up to set email alerts
|

Lifelong endurance exercise and its relation with coronary atherosclerosis

Abstract: Background and Aims The impact of long-term endurance sport participation (on top of a healthy lifestyle) on coronary atherosclerosis and acute cardiac events remains controversial. Methods The Master@Heart study is a well-balanced prospective observational cohort study. Overall, 191 lifelong master endurance athletes, 191 late-onset athletes (endurance sports initiation after 30 years of age), and 176 healthy non-athletes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In addition to satisfying the athlete’s nutritional needs and not interfering with sports performance, well-planned vegetarian diets (i.e., lacto-ovo and vegan) can be beneficial for the athlete’s health, potentially counteracting their higher risk of ischemic heart disease (IHD) [ 34 ]; the scientific literature reports that a vegetarian diet is associated with a reduction in the risk of IHD by 25% [ 92 ], and that, in general, the health benefits are greater in vegetarians than in nonvegetarians [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to satisfying the athlete’s nutritional needs and not interfering with sports performance, well-planned vegetarian diets (i.e., lacto-ovo and vegan) can be beneficial for the athlete’s health, potentially counteracting their higher risk of ischemic heart disease (IHD) [ 34 ]; the scientific literature reports that a vegetarian diet is associated with a reduction in the risk of IHD by 25% [ 92 ], and that, in general, the health benefits are greater in vegetarians than in nonvegetarians [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2009 German study had already found myocardial damage in 12% of a group of marathon runners over 50 years old, against 4% of controls chosen among sedentary peers [ 33 ]. A very recent study described that lifelong endurance athletes had more coronary plaques, including more noncalcified plaques in proximal segments, than fit and healthy individuals with a similarly low cardiovascular risk profile [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is a major contributor to heart attack and stroke. Atherosclerotic plaque can upregulate antiphagocytic CD47 signaling, which would block immune clearance by macrophages through the CD47-SIRPα-SHP-1 signaling axis and facilitate sustained plaque expansion. However, antibody-based systemic therapies that block CD47 signaling might exert adverse effects on healthy tissues, such as eliminating surrounding red blood cells to generate ischemia . Safety concerns have thus become a key barrier to the clinical translation of such drugs.…”
Section: Application Of Nanomedomicsmentioning
confidence: 99%
“…The benefits of exercise for curbing risk factors for atherosclerosis and reducing overall cardiovascular morbidity and mortality are widely recognized 1,2 , however, several studies have shown an increased burden of coronary atherosclerosis in male master athletes [3][4][5][6] . Whereas original studies reported increased coronary artery calcification (CAC) in male marathon runners with a relatively high prevalence of atherosclerotic risk factors 4 , recent studies have shown similar findings in male master athletes with a low atherosclerotic risk profile 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of exercise for curbing risk factors for atherosclerosis and reducing overall cardiovascular morbidity and mortality are widely recognized 1,2 , however, several studies have shown an increased burden of coronary atherosclerosis in male master athletes [3][4][5][6] . Whereas original studies reported increased coronary artery calcification (CAC) in male marathon runners with a relatively high prevalence of atherosclerotic risk factors 4 , recent studies have shown similar findings in male master athletes with a low atherosclerotic risk profile 3,5,6 . Increasing age, traditional risk factors and volume of exercise are major determinants of high CAC scores in males although coronary inflammation, dietary factors, blood pressure responses to exercise and serum parathyroid hormone concentrations have also been postulated [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%